Repercussions imposed by the pandemic on the care for children with mental disorders in a pediatric unit - Daniela Giotti Da Silva; Maria de Lourdes Custódio Duarte; Fabiane Machado Pavani; Alessandra Porto D'Ávila; Yanka Eslabão Garcia (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To understand the perceptions of nurses about the repercussions on the care for children with mental disorders in a pediatric inpatient unit amidst the COVID-19 pandemic. Method: Qualitative research conducted with 13 nurses in a general pediatrics unit in a large hospital in southern Brazil. Data were collected through semi-structured interviews and analyzed according to the Thematic Analysis. Results: Respondents perceived repercussions on hospital routines due to the pandemic, such as restriction of recreation activities; enforcement of social distancing; limitation of family visits; mandatory use of personal protective equipment and difficulty in counter-referral of care. Final considerations: The results characterized the moment experienced in the unit, providing the institution's managers with tools for the construction and implementation of new practices, making it possible to meet the demands of mental health care for children with mental disorders within the premises of psychosocial care.